Cyclin Dependent Kinases in Antiviral Drug Discovery - Tarasova, Olga; de Azevedo Junior, Walter Filgueira (Current Medicinal Chemistry, 2025)
Cyclin-dependent kinases that are responsible for cell cycle control, have been studied for over 30 years as therapeutic targets for the treatment of cancer and inflammation. In the past twenty years, their activities in various viral infections have been investigated in the search of novel therapeutic strategies in the treatment of viral infections. The interest in evaluating antiviral activity of cyclin-dependent kinase inhibitors is closely linked to their role as host factors in viral replication. Due to the development of viral resistance, the strategies directed toward the targeting host machinery are still under investigation. This review is dedicated to the analysis of the molecular mechanisms of viral infection control by cyclin-dependent kinases that may reveal the potential mechanisms of action for their inhibitors and regulators as antiviral agents. We also consider recent efforts and achievements in the development of potential antiviral agents based on the cyclin-dependent kinase inhibitors and regulators, including their effects on various viruses, side effects, and toxicities.
Keywords: Cyclin-dependent kinase